(untitled) (World Bulletin of Management and Law, 2022)
Throughout history, mankind has been exposed to many pandemics, including the Corona pandemic, which has completely infected the world and affected all aspects of life. This, of course, is due to the form of the epidemic, the way it spreads, and its direct impact on human life, and that addressing these epidemics is through the World Health Organization (WHO) in cooperation with the internal health authorities of countries. Thus, the basis of work is through the application of international health law, which is part of the general and specialized international law, to confront epidemics and infectious diseases, keep abreast of developments and scientific knowledge and know the causes of some infectious diseases. In addition to that work to oblige countries to implement the International Health Regulations because of their a binding legal nature, as well as their scientific role to research the new scientific concepts developed by health regulations, and to confront the health risks resulting from the Corona pandemic.